A trustworthy AI framework for retail and distribution business in Cambodia - Rambo, Sorn; Chutiporn Anutariya; Vatcharaporn Esichaikul; Chantri Polprasert; Kampot Cement Co., Ltd., Cambodia (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
This research develops a comprehensive Trustworthy AI Framework specifically tailored to Cambodia's retail and distribution sectors, aiming to ensure the responsible and ethical implementation of AI systems. The framework addresses the unique socio economic landscape of Cambodia, which includes cultural nuances, resource constraints, and evolving regulatory frameworks. By focusing on both technical and ethical dimensions, the framework provides practical guidelines for Cambodian businesses to navigate the complexities of AI adoption.The framework comprises two main key components: Ethical AI Principles and AI Governance Structure. These components are informed by insights gathered from surveys and interviews with stakeholders in Cambodia{u2019}s retail and distribution sectors. Ethical AI Principles include fairness, transparency, robustness, accountability, data privacy, human-centricity, and societal values. AI Governance Structure adopts existing frameworks like the EU AI Ethics Guidelines, OECD AI Principles, and ASEAN Guide on AI Governance and Ethics to ensure responsible AI management.Before these components can be effectively implemented, preliminary stages focusing on AI Awareness and Adoption, as well as AI Readiness Assessment, are essential. AI Awareness and Adoption emphasize educational programs and strategic planning to foster AI acceptance among stakeholders. The AI Readiness Assessment focuses on upskilling staff, evaluating infrastructure, and ensuring regulatory compliance to establish a strong foundation for AI integration.Expert evaluations integrate insights from AI ethics, business ethics, and cultural studies, empowering Cambodian enterprises to harness AI technologies responsibly. The framework aims to uphold societal values, foster consumer trust, and contribute to sustainable socio-economic development. Through practical guidelines and best practices, it addresses the ethical challenges associated with AI adoption in Cambodia{u2019}s retail and distribution sectors.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Science in Data Science and Artificial Intelligence
Research Studies Project Report (M. Sc.) - Asian Institute of Technology, 2024
Keywords: Retail trade -- Cambodia -- Data processing; Retail trade -- Cambodia -- Automation; Artificial intelligence -- Moral and ethical aspects